PENGONTROLAN AKSES INTERNET MENGGUNAKAN MODEL OTOMATA DENGAN MEMANFAATKAN LOG PROXY SERVER - Setyowibowo, Sigit; Wahyunungsih, Dian (WIDYA TEKNIKA, 2014)
Duplicatet asks owned by admin Internetin STMIK PPKIA Pradnya Paramita resulted admin Internet can not linger on the configuration computer to an Internet server so often negative sites can be accessed freely. To anticipate the necessary control to access the Internet by installing Squid proxy server. To further enhance the ability of the proxy server, can be done by analyzing the log proxy server, because the record contains a record of the users Internet access. Needed a method to read and analyze the log file because the file is recorded in the text squensial. The method used is a deterministic Turing machine is a finite state machine that has a two - way tape. Analysis of the log file will produce rules that can be read and understood by the Squid proxy server. The rules are access control list (ACL) that is then returned by the proxy server configured. Based on the results of the configurations quid ability will always be up to date and can ease the work load of the Internet admin. Â  Â  Keywords: Pengontrolan, Proxy Server, otomata, dan log proxyserver..